The Influence of Affective, Cognitive and Normative Commitment on Police Performance - Hamid, SUpardi; Earlyanti, Novi Indah (International Journal of Social and Management Studies, 2023)
The purpose of this research is to examine and analyze the effect of affective commitment on police performance, cognitive commitment on police performance and normative commitment on police performance. This type of research is quantitative research using a survey method or approach. simple random sampling. Data analysis using the Structural Equation Modeling (SEM) method with SmartPLS 3.0 software tools will be used in the model and hypothesis testing. Data were obtained by distributing online questionnaires designed with a Likert scale of 1 to 5. The stages of data analysis in this study were testing the validity, reliability and testing the hypothesis. The findings of this study are that affective commitment has a positive and significant effect on police performance, commitment cognitive has a positive and significant effect on police performance and normative commitment has a positive and significant effect on police performance.